Comparative study of fentanyl and morphine in addition to hyperbaric or isobaric bupivacaine in combined spinal anaesthesia for caesarean section - SARAÇOĞLU, AYTEN (TERMEDIA PUBLISHING HOUSE LTD, 2011)
Introduction: The aim of our study was to compare the effects of isobaric and hyperbaric bupivacaine combined with morphine or fentanyl in patients undergoing caesarean section. We assessed quality and spread of analgesia and anaesthesia, postoperative analgesic requirement and side effects. Material and methods: Hundred patients with American Society of Anesthesiologists physical status (ASA) I-II, age 18 to 40 years, were randomized to 4 groups. The intrathecal solutions were isobaric bupivacaine + morphine (group A), isobaric bupivacaine + fentanyl (group B), heavy bupivacaine + + morphine (group C) and heavy bupivacaine + fentanyl (group D). Mean arterial pressure, heart rate, oxygen saturation, ephedrine consumption, analgesic requirement time and additional analgesic needs were recorded. Results: The 1(st) min value of mean arterial pressure was the lowest one in all groups. Heart rate decreased significantly in group A at the 10(th) min but not in the other groups. The decrease of visual analogue scale (VAS) pain scores began in the groups after the 4(th) postoperative h (p < 0.05) and the VAS value of group B at the 8(th) h was significantly higher than the other groups. The first analgesic requirement time in the postoperative period was longer in patients who had intrathecal morphine than those who had fentanyl. The duration of analgesia with isobaric bupivacaine and morphine was the longest one. Conclusions: We concluded that intrathecal morphine provides a long duration of postoperative analgesia but the duration gets longer when it is combined with plain bupivacaine instead of heavy bupivacaine.
Keywords: opioid; combined spinal; caesarean; analgesia; bupivacaine; INTRATHECAL BUPIVACAINE; BARICITY; SURGERY; OPIOIDS; SPREAD; HUMANS